Acting Out Philosophy - Rudl, Matevž (Od filozofije poučevanja do poučevanja filozofije: Festschrift Rudi Kotnik, 2025)
In this paper, the nature of teaching philosophy is analysed. The teaching of character-forming subjects should be neutral. The teacher should present opposing theories with equal passion. The views that claim that the goal of teaching philosophy was carving out a human form are false. The teacher should not decide which theory is true. He must not guide the students. This normative claim is justified with two observations. First, there are many incompatible philosophical theories. Second, there are many ideas about when a person becomes actualised. It has to be left to the student to come to terms with all the theories. Some concepts associated with the concept of Bildung imply a disputable role of the teacher because they limit the freedom of students and may lead to an authoritarian and/or totalitarian society. Such is the concept of discursive thinking as a natural development of thought. Mill’s criterion of truth in human sciences is presented.